2022
DOI: 10.1371/journal.pone.0261773
|View full text |Cite
|
Sign up to set email alerts
|

Compounding inequalities: Adolescent psychosocial wellbeing and resilience among refugee and host communities in Jordan during the COVID-19 pandemic

Abstract: Purpose The COVID-19 pandemic and associated risk-mitigation strategies have altered the social contexts in which adolescents in low- and middle-income countries live. Little is known, however, about the impacts of the pandemic on displaced populations, and how those impacts differ by gender and life stage. We investigate the extent to which the pandemic has compounded pre-existing social inequalities among adolescents in Jordan, and the role support structures play in promoting resilience. Methods Our analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 71 publications
2
41
1
Order By: Relevance
“…Our results from school-attending adolescents in post-con icts areas are in line with emerging evidence that suggests multiple domains of adolescents' psychosocial wellbeing were negatively impacted by the pandemic. Our ndings also agree with other studies of regions affected by armed con ict, where an increase in the prevalence of mental health disorders in young populations has been found (5,7,30,37,38).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results from school-attending adolescents in post-con icts areas are in line with emerging evidence that suggests multiple domains of adolescents' psychosocial wellbeing were negatively impacted by the pandemic. Our ndings also agree with other studies of regions affected by armed con ict, where an increase in the prevalence of mental health disorders in young populations has been found (5,7,30,37,38).…”
Section: Discussionsupporting
confidence: 93%
“…Measures to reduce the spread of the virus-such as lockdowns, physical distancing and school closures-have not only altered family and peer relationships and distanced young people from social spaces like classrooms and games, but also disrupted daily routines and their learning process and education. All of these changes might translate into mental health repercussions which can be particularly profound in vulnerable adolescents who are victims of armed con ict and forced displacement (7).…”
Section: Introductionmentioning
confidence: 99%
“…Other similar studies have shown how the COVID-19 outbreak and the related risk-reduction strategies have changed the social contexts of adolescents in low- and middle-income countries, with profound implications for their well-being, especially in the case of vulnerable adolescents, including those affected by poverty and armed conflict. In such contexts, pre-existing conditions of disadvantage have had a negative impact on the mental health of adolescents, especially that of girls 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that COVID-19 has had severe compounding effects on existing inequalities. Rates of food insecurity and hunger, unemployment, anxiety and social isolation are on the rise and threaten the social fabrics holding refugee communities together as violent conflicts persist [8][9][10]. This may have long-term effects far beyond the pandemic period.…”
Section: Box 1 Managing Covid-19 In Refugee Camps and Informal Settle...mentioning
confidence: 99%